1998
DOI: 10.1086/301699
|View full text |Cite
|
Sign up to set email alerts
|

Ataxia with Isolated Vitamin E Deficiency: Heterogeneity of Mutations and Phenotypic Variability in a Large Number of Families

Abstract: Ataxia with vitamin E deficiency (AVED), or familial isolated vitamin E deficiency, is a rare autosomal recessive neurodegenerative disease characterized clinically by symptoms with often striking resemblance to those of Friedreich ataxia. We recently have demonstrated that AVED is caused by mutations in the gene for alpha-tocopherol transfer protein (alpha-TTP). We now have identified a total of 13 mutations in 27 families. Four mutations were found in >=2 independent families: 744delA, which is the major mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
184
2
10

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 288 publications
(202 citation statements)
references
References 30 publications
6
184
2
10
Order By: Relevance
“…α-T is also required for the health of human CNS. This is vividly demonstrated in Ataxia with Vitamin E Deficiency (AVED) patients who present with neurological symptoms of varying severity (Cavalier et al, 1998;Gotoda et al, 1995;Schuelke et al, 1999;Tamaru et al, 1997). Neurological deficits similar to those of the AVED subjects are also observed in transgenic mice with a deletion of the α-TTP gene (Yokota et al, 2001;Yokota et al, 1987).…”
Section: Introductionmentioning
confidence: 91%
“…α-T is also required for the health of human CNS. This is vividly demonstrated in Ataxia with Vitamin E Deficiency (AVED) patients who present with neurological symptoms of varying severity (Cavalier et al, 1998;Gotoda et al, 1995;Schuelke et al, 1999;Tamaru et al, 1997). Neurological deficits similar to those of the AVED subjects are also observed in transgenic mice with a deletion of the α-TTP gene (Yokota et al, 2001;Yokota et al, 1987).…”
Section: Introductionmentioning
confidence: 91%
“…a-Tocopherol levels are also affected by genetic variants. Mutations in liver a-tocopherol transfer protein result in human a-tocopherol deficiency (14). It is also reported that human plasma levels of a-tocopherol but not g-tocopherol are increased in male adults and children by the apolipoprotein A5 1131T.C gene polymorphism (15,16).…”
mentioning
confidence: 99%
“…Age of onset usually varied from 4 to 20 years, with outliers ranging from 2 to 52 years 24,25 . Clinical manifestations are characterized by progressive trunk and limbs ataxia, dysarthria, disturbance of positional and vibratory lower limbs senses, Babinski sign and abolished deep tendon reflexes.…”
Section: Ataxia With Vitamin E Deficiencymentioning
confidence: 99%
“…Clinical manifestations are characterized by progressive trunk and limbs ataxia, dysarthria, disturbance of positional and vibratory lower limbs senses, Babinski sign and abolished deep tendon reflexes. Scoliosis and pes cavus are commonly seen [24][25][26] , yet retinopathy is less frequent 25,26 . Dystonia (13%) and head titubation (28%) are more commonly seen in AVED than in FA 24,26 .…”
Section: Ataxia With Vitamin E Deficiencymentioning
confidence: 99%
See 1 more Smart Citation